Analysis of mood levels in cricket athletes during the training phase based on gender - Nuraziz, Yuga; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problems: Mood significantly influences athletic performance, particularly in cricket, where monotonous and repetitive training can negatively affect athletes’ moods, reduce motivation, and ultimately impair on-field performance. Negative moods are not only detrimental to individual athletes but can also spread among teammates, amplifying their impact. Purpose: This study aimed to examine differences in mood levels between male and female cricket athletes during training, focusing on how gender may influence emotional responses in this context. Methods: This research utilized the Brunel Mood States (BRUMS) questionnaire, which was administered to the sample participants just once. Data analysis for the study was conducted using a t-test in SPSS version 25. Results: The results indicated significant differences in mood levels between male and female cricket athletes. Specifically, there were considerable disparities in negative mood states, such as tension, depression, anger, fatigue, and confusion, between the two groups during the training phase. Despite these differences, both male and female athletes exhibited an